Fused-Ring Derivatives of Quinoxalines: Spectroscopic Characterization and Photoinduced Processes Investigated by EPR Spin Trapping Technique - Barbieriková, Zuzana (Molecules, 2014)
10-Ethyl-7-oxo-7,10-dihydropyrido[2,3-f]quinoxaline derivatives, synthesized as promising biologically/photobiologically active compounds were characterized by UV/vis, FT-IR and fluorescent spectroscopy. Photoinduced processes of these derivatives were studied by EPR spectroscopy, monitoring in situ the generation of reactive intermediates upon UVA (λ(max) = 365 nm) irradiation. The formation of reactive oxygen species and further oxygen- and carbon-centered radical intermediates was detected and possible reaction routes were suggested. To quantify the investigated processes, the quantum yields of the superoxide radical anion spin-adduct and 4-oxo-2,2,6,6-tetramethylpiperidine N-oxyl generation were determined, reflecting the activation of molecular oxygen by the excited state of the quinoxaline derivative.